2018
DOI: 10.3390/md16120460
|View full text |Cite
|
Sign up to set email alerts
|

Orthosteric and/or Allosteric Binding of α-Conotoxins to Nicotinic Acetylcholine Receptors and Their Models

Abstract: α-Conotoxins from Conus snails are capable of distinguishing muscle and neuronal nicotinic acetylcholine receptors (nAChRs). α-Conotoxin RgIA and αO-conotoxin GeXIVA, blocking neuronal α9α10 nAChR, are potential analgesics. Typically, α-conotoxins bind to the orthosteric sites for agonists/competitive antagonists, but αO-conotoxin GeXIVA was proposed to attach allosterically, judging by electrophysiological experiments on α9α10 nAChR. We decided to verify this conclusion by radioligand analysis in competition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…The binding capacity (IC 50 values) was estimated in competition with the radioiodinated α-bungarotoxin [prepared as described in Kryukova et al (2018) with specific radioactivity of 500 Curies/mmol] for association with the membrane-bound Torpedo californica nAChR (Hucho et al, 1978) (kindly provided by Prof. F. Hucho, Institute for Chemistry and Biochemistry, Freie Universität Berlin, Germany), human α7 nAChR stably expressed in the rat pituitary tumor-derived cell line GH4C1 (Virginio et al, 2002) (received from Eli Lilly and Company, London, UK), LBD of the human nAChR α9 subunit (Zouridakis et al, 2014) (prepared in the laboratory of Prof. S. Tzartos, Department of Neurobiology, Hellenic Pasteur Institute, Greece), and AChBP from Aplysia californica (Lin et al, 2014) (kindly provided by Prof. S. Luo, Key Laboratory for Marine Drugs of Haikou, Hainan University, China).…”
Section: Methodsmentioning
confidence: 99%
“…The binding capacity (IC 50 values) was estimated in competition with the radioiodinated α-bungarotoxin [prepared as described in Kryukova et al (2018) with specific radioactivity of 500 Curies/mmol] for association with the membrane-bound Torpedo californica nAChR (Hucho et al, 1978) (kindly provided by Prof. F. Hucho, Institute for Chemistry and Biochemistry, Freie Universität Berlin, Germany), human α7 nAChR stably expressed in the rat pituitary tumor-derived cell line GH4C1 (Virginio et al, 2002) (received from Eli Lilly and Company, London, UK), LBD of the human nAChR α9 subunit (Zouridakis et al, 2014) (prepared in the laboratory of Prof. S. Tzartos, Department of Neurobiology, Hellenic Pasteur Institute, Greece), and AChBP from Aplysia californica (Lin et al, 2014) (kindly provided by Prof. S. Luo, Key Laboratory for Marine Drugs of Haikou, Hainan University, China).…”
Section: Methodsmentioning
confidence: 99%
“…This means that at least relatively long oligoarginine peptides can bind to this nAChR model. We recently demonstrated a competition of 125 I-aBgt with arginine-rich a-conotoxin RgIA and aO-conotoxin GeXIVA for binding to another nAChR model, namely to the LBD of the nAChR a9 subunit (a9 LBD) (Kryukova et al, 2018a). In this work, we checked the interaction of oligoarginines with a9 LBD via their ability to inhibit specific 125 I-aBgt binding ( Fig.…”
Section: Resultsmentioning
confidence: 95%
“…In our recent work on low molecular weight compounds (Kudryavtsev et al, 2018;Spirova et al, 2019), a-conotoxins (Kudryavtsev et al, 2015;Kasheverov et al, 2016;Kryukova et al, 2018a), and human Ly6 proteins (Lyukmanova et al, 2016;Durek et al, 2017), we found that some of them can bind to the orthosteric or allosteric sites of nAChRs. Here we did not plan a detailed investigation of the mechanism of oligoarginine action, but we made exceptions for R8 and W2R4.…”
Section: Discussionmentioning
confidence: 97%
“…The α-conotoxins from the A superfamily target various subtypes of nicotinic acetylcholine receptors [ 30 , 31 , 32 ], which have a wide distribution in cone snails. Surprisingly, only three precursors of α-conotoxins Lt020, Lt021 and Lt022 with type I cysteine framework of CC-C-C were identified in C. litteratus transcriptomes, which belong to the α4/7 subfamily with CC-X4-C-X7-C mode.…”
Section: Discussionmentioning
confidence: 99%